Biomimetic coatings enhance tribocorrosion behavior and cell responses of commercially pure titanium surfaces - da Silva Vieira Marques, Isabella; Alfaro, Maria Fernanda; Saito, Miki Taketomi; da Cruz, Nilson Cristino [UNESP]; Takoudis, Christos; Landers, Richard; Mesquita, Marcelo Ferraz; Nociti, Francisco Humberto; Mathew, Mathew T.; Sukotjo, Cortino; Barão, Valentim Adelino Ricardo (My University, 2016)
Biofunctionalized surfaces for implants are currently receiving much attention in the health care sector. Our aims were (1) to create bioactive Ti-coatings doped with Ca, P, Si, and Ag produced by microarc oxidation (MAO) to improve the surface properties of biomedical implants, (2) to investigate the TiO2 layer stability under wear and corrosion, and (3) to evaluate human mesenchymal stem cells (hMSCs) responses cultured on the modified surfaces. Tribocorrosion and cell experiments were performed following the MAO treatment. Samples were divided as a function of different Ca/P concentrations and treatment duration. Higher Ca concentration produced larger porous and harder coatings compared to the untreated group (p<0.001), due to the presence of rutile structure. Free potentials experiments showed lower drops (-0.6 V) and higher coating lifetime during sliding for higher Ca concentration, whereas lower concentrations presented similar drops (-0.8 V) compared to an untreated group wherein the drop occurred immediately after the sliding started. MAO-treated surfaces improved the matrix formation and osteogenic gene expression levels of hMSCs. Higher Ca/P ratios and the addition of Ag nanoparticles into the oxide layer presented better surface properties, tribocorrosive behavior, and cell responses. MAO is a promising technique to enhance the biological, chemical, and mechanical properties of dental implant surfaces.